Effects of Work Shifts and Mental Workload on Chronic Fatigue among Female Nurses in Intensive Care Units - samira mirzaei; Zahra Zamanian; Jafar Hasan Zade (Journal of Health Sciences and Surveillance System, 2015)
Background: The present study aimed to investigate the effects of work shifts and mental workload on chronic fatigue among female nurses in Intensive Care Units of selected hospitals in Shiraz. Methods: The participants in this cross-sectional study were 118 female nurses working in Intensive Care Units of three hospitals in Shiraz with an average age of 304.8± years. SP (Samn-Perelli) Mental fatigue scale and NASA task load index were rated for two weeks at the beginning and end of each work shift. The Checklist Individual Strenght (CIS) questionnaire was completed to assess the fatigue during the last two weeks. Results: Mean score of chronic fatigue was 69.2±13. Menal fatigue and mental workload per shift were significantly correlated with work shifts (P=0.001). Mental workload (P=0.006, r=0.24) and mental fatigue caused by work shifts (P=0.001, r=0.42) were also significantly correlated with chronic fatigue. Conclusion: The results of the study showed that mental workload and work shifts influence the nurses’ fatigue in Intensive Care Units. Therefore, using intervention strategies to reduce mental work load and modification of shift work system in this group seems to be necessary.